2020
DOI: 10.1007/s00066-020-01657-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of low-risk prostate cancer: a retrospective study with 477 patients comparing external beam radiotherapy and I-125 seeds brachytherapy in terms of biochemical control and late side effects

Abstract: Purpose The goal of our study was comparison of external beam radiotherapy (EBRT) and I‑125 seeds brachytherapy in terms of biochemical control and development of late gastrointestinal and genitourinary side effects. Patients and methods 477 low-risk prostate cancer patients treated between 2000 and 2019 at our department using either I‑125 seeds brachytherapy or EBRT with a dose of 74 or 78 Gy were reviewed for our analysis. 213 patients were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Regarding late side effects, we observed reduced genitourinary side effects and increased gastrointestinal side effects for EBRT in comparison to seeds. This resembles the results in our low-risk collective [3]. For maximum side effects, we noticed a significant increase for late genitourinary side effects in patients treated with 78 Gy compared to 74 Gy.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding late side effects, we observed reduced genitourinary side effects and increased gastrointestinal side effects for EBRT in comparison to seeds. This resembles the results in our low-risk collective [3]. For maximum side effects, we noticed a significant increase for late genitourinary side effects in patients treated with 78 Gy compared to 74 Gy.…”
Section: Discussionsupporting
confidence: 87%
“…Localized primary prostate cancer can be treated via external beam radiotherapy (EBRT) or permanent interstitial seed brachytherapy (BT). Both of these treatment modalities achieve excellent tumor control rates [1][2][3]. The recommendations and guidelines consider these modalities as equivalent especially for patients with low-risk prostate cancer [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we replaced it with HDG10.01 B (2,134 points for patients >74 years old) and HDG10.01 C (1,381 points for patients ≤74 years old) for prostate cancer. As the median age of patients is <75 years ( 13 15 ), we decided to use HDG10.01 C for further calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Advantages of surgery and brachytherapy are the one-time intervention, whereas EBRT, even in moderately hypofractionated schedules, takes place over 3–4 weeks, though one-time stereotactic treatments are being evaluated ( 23 ). Regarding side effects, EBRT leads to more gastrointestinal side effects but less urinary incontinence and erectile dysfunction within the first 5 years compared to surgery ( 24 ), whereas brachytherapy leads to more genitourinary, but less gastrointestinal, toxicity compared to EBRT ( 13 ). These facts have to be evaluated, as treatment costs for all modalities in low- and intermediate-risk prostate cancer are well below 10,000 € per treatment, even at the University Hospital Vienna, and side effects may persist for up to at least 5 years ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding toxicity, we found that the association of EBRT and seeds supposes a greater risk of urological (from 16.9% to 26.1%) and rectal complications (from 2.5% to 10.1%). Generally, the use of external RT increases the risk of digestive toxicity [ 31 ]. Even so, urological G3 toxicity occurs only in 5.8% and rectal G3 toxicity in one case, fewer than the data published in the ASCENDE-RT study (only 6% of toxicity was persistent) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%